Do Advanced Glycation End Products and Its Receptor Play a Role in Pathophysiology of Hypertension? - Prasad, Kailash (Int J Angiol, 2017)
There is a close relationship between arterial stiffness and blood pressure. The studies suggest that the advanced glycation end products (AGEs) and its cell receptor (RAGE) are involved in the arterial stiffness in two ways: changes in arterial structure and vascular function. Plasma levels of AGEs and expression of RAGE are elevated, while the levels of soluble RAGE (sRAGE) and endogenous secretory RAGE (esRAGE) are lowered in patients with hypertension (HTN). There is a positive correlation between plasma levels of AGEs and arterial stiffness, and an inverse association between arterial stiffness/HTN, and serum levels of sRAGE and esRAGE. Various measures can reduce the levels of AGEs and expression of RAGE, and elevate sRAGE. Arterial stiffness and blood pressure could be reduced by lowering the serum levels of AGEs, and increasing the levels of sRAGE. Levels of AGEs can be lowered by reducing the consumption of AGE-rich diet, short duration of cooking in moist heat at low temperature, and cessation of cigarette smoking. Drugs such as aminoguanidine, vitamins, angiotensin-converting enzyme (ACE) inhibitors, angiotensin-II receptor blockers, statins, and metformin inhibit AGE formation. Alagebrium, an AGE breakers reduces levels of AGEs. Clinical trials with some drugs tend to reduce stiffness. Systemic administration of sRAGE has beneficial effect in animal studies. In conclusion, AGE–RAGE axis is involved in arterial stiffness and HTN. The studies suggest that inhibition of AGEs formation, reduction of AGE consumption, blockade of AGE–RAGE interaction, suppression of RAGE expression, and exogenous administration of sRAGE may be novel therapeutic strategies for treatment of arterial stiffness and HTN.